Comparative Evaluation of Melatonin as an Alternative Therapy in Tinnitus: A Double-Blind, Placebo-Controlled Randomized Trial - Barati, Behrouz; Asadi, Mahboobe; Rahimipour, Niloufar (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2022)
Background: Tinnitus is an auditory perception that is described as a perception of noise without any external acoustic stimulant. Tinnitus causes many problems including sleep disturbances and difficulty in concentrating for patients. Aim: In this trial, we evaluated melatonin as an alternative therapy in tinnitus. Methods: In this clinical trial, tinnitus patients (n = 90) were randomly assigned to 12 weeks of double-blind treatment with melatonin (n = 30) at a fixed-dose (3 mg once daily), sertraline (n = 30) at a fixed dose (50 mg once daily) and placebo (n = 30) once daily. The treatment outcomes were measured using THI (Tinnitus Handicap Inventory), tinnitus loudness score, and tinnitus awareness score after 3 months. Results: The baseline assessment with THI (Tinnitus Handicap Inventory) showed no significant difference in THI score between groups before treatment (p-value = 0.38). The mean THI score shows a significant decrease in both melatonin and sertraline groups (p-value < 0.03). Overall, a mean of 20% decrease in tinnitus loudness score and a 2-fold decrease in tinnitus awareness score was seen in the melatonin group. In contrast, a mean of 2% decrease in tinnitus loudness score and 25% decrease in tinnitus awareness score was seen in the sertraline group. Conclusion: Both melatonin and sertraline reduce tinnitus loudness score and tinnitus awareness score within 12 weeks in primary care, but melatonin showed a more significant outcome. Our findings support the prescription of melatonin in tinnitus management.